Collapse of an arctic bird community resulting from ungulate-induced loss of erect shrubs - Ims, Rolf Anker; Henden, John-André (Biological Conservation, 2012)
Rapid, but contrasting, changes in the extent of erect thicket-forming shrubs is presently seen in the Arctic, either resulting from a warmer climate (increasing extent) or intensified herbivory (decreasing extent). We investigated the impact of loss of willow shrubs on a bird community in arctic riparian sediment plains in northern Norway subject to varying intensities of reindeer browsing. In riparian habitats where willow thickets had been lost, bird species richness was more than halved compared to habitats where some patches of thickets were still present. As could be expected species previously suggested to use erect woody vegetation as nesting places and/or foraging habitats were most consistently impacted. However, even some open ground habitat specialists appeared to be negatively impacted, possibly due to loss of spatial spill-over effects of insects from willow thickets. To preserve low-arctic avian biodiversity in a warming climate, management should strive to identify levels of ungulate browsing that strike the balance between shrub-encroached and shrub-denuded arctic tundra